If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2y + 1) + 3(4y + -3) = 50 + -2(4y + -3) Reorder the terms: 5(1 + 2y) + 3(4y + -3) = 50 + -2(4y + -3) (1 * 5 + 2y * 5) + 3(4y + -3) = 50 + -2(4y + -3) (5 + 10y) + 3(4y + -3) = 50 + -2(4y + -3) Reorder the terms: 5 + 10y + 3(-3 + 4y) = 50 + -2(4y + -3) 5 + 10y + (-3 * 3 + 4y * 3) = 50 + -2(4y + -3) 5 + 10y + (-9 + 12y) = 50 + -2(4y + -3) Reorder the terms: 5 + -9 + 10y + 12y = 50 + -2(4y + -3) Combine like terms: 5 + -9 = -4 -4 + 10y + 12y = 50 + -2(4y + -3) Combine like terms: 10y + 12y = 22y -4 + 22y = 50 + -2(4y + -3) Reorder the terms: -4 + 22y = 50 + -2(-3 + 4y) -4 + 22y = 50 + (-3 * -2 + 4y * -2) -4 + 22y = 50 + (6 + -8y) Combine like terms: 50 + 6 = 56 -4 + 22y = 56 + -8y Solving -4 + 22y = 56 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. -4 + 22y + 8y = 56 + -8y + 8y Combine like terms: 22y + 8y = 30y -4 + 30y = 56 + -8y + 8y Combine like terms: -8y + 8y = 0 -4 + 30y = 56 + 0 -4 + 30y = 56 Add '4' to each side of the equation. -4 + 4 + 30y = 56 + 4 Combine like terms: -4 + 4 = 0 0 + 30y = 56 + 4 30y = 56 + 4 Combine like terms: 56 + 4 = 60 30y = 60 Divide each side by '30'. y = 2 Simplifying y = 2
| 5/7=1/1-2 | | 4x+9i=0 | | 0.7x=7.49 | | 3x-3y-15=0 | | logx+log(x+5)-2=0 | | 49.77=0.3x | | 4/5x=3.6 | | X/2.4=1.29 | | 7m=-147 | | 3694.50=3600.00(1+0.75r) | | 5/11=x-2/1-3 | | ((8y/x^2)*(5x^5y/4y^5)) | | 2.5(x+2)+4.5+1.5(x-3)=13 | | 10000=(x*.39)+x | | 2u-8=28 | | 1.7x=20.91 | | 3p+10=46 | | -2(y+3)=6y-1+2(5y+5) | | 1.03+x=.5 | | -1/3=-3/5y-3/2 | | 2x+15+3x-20+60=180 | | .7x=49.14 | | 2/3-1/4x4/9 | | -1/3=3/5y-3/2 | | X-3/4=7/12 | | 10402.50=9500[1+r(1)] | | 10x^3+7=87 | | 6x+7=8x-16 | | -017+(-3.546)= | | -3(-7y+7)-5y=4(y-7)-7 | | 152+13x+8+10x+6=180 | | 5n+23=38 |